Heliox for mechanically ventilated newborns with bronchopulmonary dysplasia. Issue 2 (15th November 2013) - Szczapa, Tomasz; Gadzinowski, Janusz; Moczko, Jerzy; Merritt, T Allen
Abstract : Objective: We assessed the safety and studied the influence of short-term helium–oxygen (heliox) mechanical ventilation (MV) on respiratory function, gas exchange and oxygenation in infants with bronchopulmonary dysplasia (BPD) or at high risk for BPD. Design: A pilot, time-series study. Setting: Neonatal intensive care unit. Patients: Infants with severe BPD who required MV. Interventions: MV with helium–oxygen and air–oxygen mixtures. Main outcome measures: Respiratory parameters, acid–base balance, oxygenation and vital signs were recorded at five time points: initially during MV with air–oxygen, after 15 and 60 min of helium–oxygen MV, and 15 and 60 min after return to air–oxygen MV. Results: 15 infants with BPD were enrolled. Helium–oxygen MV was well tolerated and was associated with a statistically significant increase in tidal volume, dynamic compliance and peak expiratory flow rate. An improvement in oxygenation and a decrease in fraction of inspired oxygen was also observed. During helium–oxygen MV there was a significant decrease in the oxygenation index and alveolar–arterial oxygen tension difference. The PaO2 /fraction of inspired oxygen (FiO2 ) ratio increased significantly during helium–oxygen ventilation. A decrease in PaCO2 and an increase in pH were also observed during helium–oxygen administration, however this was not statistically significant. After ventilation with helium–oxygen was discontinued, the infants' respiratory function and oxygenation deteriorated and supplemental oxygen requirements increased accordingly. Conclusions: Helium–oxygen MV is safe and resulted in improvement of respiratory function and oxygenation in infants with severe BPD requiring MV.